ANALISA PENGARUH MARKETING CAPABILITIES TERHADAP BRAND EQUITY DAN FINANCIAL PERFORMANCE PADA INDUSTRI PERHOTELAN DI SURABAYA - Cynthia Priskilla Handoyo; Saarce Elsye Hatane (Business Accounting Review, 2016)
ABSTRACT This study aimed to examine the direct and significant affect of marketing capabilities to brand equity; brand equity to financial performance; and marketing capabilities to financial performance in hotel industry in Surabaya. This study used a quantitative approach, and the data were obtained by distributing questionnaires to hotel industry in Surabaya and then processed by using smartPLS software. This study showed that there was positive and significant relationship of marketing capabilities to brand equity; brand equity to financial performance; and marketing capabilities to financial performance in hotel industry in Surabaya.